1973
DOI: 10.1021/j100626a006
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerization pathways in the visually important polyenes. I. Retinals

Abstract: Publication costs assisted by The U. S. Atomic Energy CommissionThe photoisomerization of all-trans, 13-cis-, and 11-cis-retinal was carried out using energy transfer techniques. In this way the isomerization was initiated in the retinal triplet state. From the triplet the quantum efficiencies found were 0.17 and 0.35 for the all-trans and 13-cis isomer, values comparable to the efficiencies measured by direct singlet irradiations; however, 11-cis-retinal had a measured triplet isomerization efficiency of 0.75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The laser-induced ground-state bleaching behavior for prephotolyzed and unphotolyzed retinal solutions implies that there is a significant solvent effect in the isomerization of retinal via the triplet state. In a non-polar solvent such as MCH, the irradiation of trans retinal is expected to yield almost exclusively the 13-cis isomer (Raubach and Guzzo, 1973). In methanol, the structures of the isomerized products are not known, but they are likely to consist predominantly of one of the monocis isomers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The laser-induced ground-state bleaching behavior for prephotolyzed and unphotolyzed retinal solutions implies that there is a significant solvent effect in the isomerization of retinal via the triplet state. In a non-polar solvent such as MCH, the irradiation of trans retinal is expected to yield almost exclusively the 13-cis isomer (Raubach and Guzzo, 1973). In methanol, the structures of the isomerized products are not known, but they are likely to consist predominantly of one of the monocis isomers.…”
Section: Discussionmentioning
confidence: 99%
“…In both solvents the excitation conditions were such (laser intensity > 1 MW) that a high ( > SO per cent) conversion to the triplet state was achieved. Based on the known isomerization quantum yields (Raubach and Guzzo, 1973;Kropf and Hubbard, 1970), one can estimate that, in MCH, no more than 20 per cent cis isomer will result from laser excitation of the trans retinal solution. Using the extinction coefficients for the retinal isomers (Kropf and Hubbard, 1970), it can be shown that this amounts to only a ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ever since the recognition of the importance of geometric isomerism in vision, much effort has gone into studies of photoisomerization of retinal. Some of the recent studies are those by Kropf and Hubbard (1970), Raubach and Guzzo (1973), Waddell et al (1976), Fischer and Weiss (1974), and Rosenfeld et al (1974). In the last two papers, results of flash photolytic studies as well as chemical data were reported.…”
Section: Introduc3ionmentioning
confidence: 99%
“…Coupled with an analysis of oxygen effects, this led to the postulation of a mechanism in which isomerisation is taking place from non-relaxed vibronic triplet levels. Another study [21] puts the yield of 11 -cis retinal isomerisation following sensitisation with biacetyl as high at 75%. The discrepancy may be due to radicals formed in the photolysis of biacetyl [23].…”
Section: Isoinerisationmentioning
confidence: 99%